Feasibility Test for Multimedia Learning in Mu'allimin Muhammadiyah Madrasah of Yogyakarta, Indonesia - Arqam, Muhammad Lailan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study discusses about the feasibility test for multimedia learning in Mu’allimin Muhammadiyah madrasah of Yogyakarta, Indonesia. The results shows that the multimedia developed has an attraction that can bring out and increase student interest and motivation. While a total of 26 students in other words a total of 87% of the trial subjects used chose the "No" assessment criteria for the component of the difficulty level. As well as 13% or 4 other students say "yes". This shows that the developed multimedia learning is easy to understand and helps students to understand the kemuhammadiyahan learning material. A total of 24 students using trial subjects chose the "Yes" assessment criteria for the benefits of learning multimedia, if used in the form of a percentage it showed an amount of 80%. Students feel more helpful in learning with the emergence of a sense of comfort in learning using multimedia learning developed. And they can improve learning outcomes on kemuhammadiyahan subjects. While 20% of students answered "No", considering multimedia did not help in the learning process.